Assessing the Readiness of Lecturers and Students in Adapting to Online Learning in Vocational Higher Education - Utami, Sri; Suprianti, Yanti (Humaniora: Journal of Indonesia Culture and Society, 2022)
The research aimed to identify the teaching experience carried out by lecturers in vocational higher education, Department of Energy Conversion Engineering, dominated by practical lectures during online learning. Online learning carried out during the pandemic was one of the efforts to manage the learning process to suppress the coronavirus's spread (COVID-19). In the learning process, which involved students and lecturers, limitations were not only felt by students as participants in the learning process but also by lecturers who were in charge of the courses. Activities in the laboratory were undertaken at all levels and accounted for more than 40% of all learning activities. The experience of the online teaching process for vocational engineering education was very interesting to be researched since the challenges of delivering practical material had a 50% proportion of the entire course. Observations on laboratory activities during online lectures could be a reference for further learning activities. Qualitative methods were used by observation, data collection and compilation, and analysis. From the data that have been accumulated, it can be concluded that several components become obstacles in the online learning process for engineering/vocational higher education. However, some parts are also considered beneficial during the learning process for the lecturers and students.Â